Perinatal Depressive Symptoms, Human Immunodeficiency Virus (HIV) Suppression, and the Underlying Role of Antiretroviral Therapy Adherence: A Longitudinal Mediation Analysis in the IMPAACT P1025 Cohort. (13th May 2021) - Momplaisir, Florence; Hussein, Mustafa; Kacanek, Deborah; Brady, Kathleen; Agwu, Allison; Scott, Gwendolyn; Tuomala, Ruth; Bennett, David
Abstract: Background: Women with HIV have higher risk of depressive symptoms in the perinatal period. Evidence on how perinatal depressive symptoms affect viral suppression (VS) and adherence to antiretroviral therapy (ART) remains limited. Methods: Perinatal depressive symptoms were assessed using 6 items from the AIDS Clinical Trials Group (ACTG) Quality of Life questionnaire. VS (viral load <400 copies/mL) was the outcome. Adherence was defined as no missed dose in the past 1–4 weeks using the ACTG Adherence Questionnaire. Generalized mixed-effects structural equation models estimated the association of depressive symptoms on VS and the mediating role of ART adherence among women enrolled in the IMPAACT P1025 Perinatal Core Protocol (2002–2013). Results: Among 1869 participants, 47.6% were 21–29 years, 57.6% non-Hispanic Black. In the third trimester, the mean depressive symptoms score was 14.0 (±5.2), 68.0% had consistent adherence, and 77.3% achieved VS. At 6 months postpartum, depressive symptoms declined while adherence and VS fell to 59.8% and 53.0%, respectively. In the fully adjusted model, a 1-SD increase in depressive symptoms was associated with a 3.8-percentage-point (95% CI: −5.7, −1.9) decline in VS. This effect is the sum of the indirect effect of depressive symptoms on VS via ART adherence (−0.4; 95% CI: −.7, −.2) and the direct effect through other pathways (−3.4; −5.2, −1.5). The decline in adherence driven by depressive symptoms accounted for ≥11% of the total negative effect of depressive symptoms on VS. Conclusions: Perinatal depressive symptoms were associated with decreased adherence and VS, highlighting the need to screen for, diagnose, and treat perinatal depression to optimize maternal outcomes. Clinical Trials Registration: NCT00028145. Abstract : In this longitudinal analysis of pregnant and postpartum women with HIV, we found that perinatal depressive symptoms were associated with lower adherence and lower viral suppression.